Who Can You Trust? The Impact of Procedural Justice, Trust, and Police Officer Sex on Women's Sexual Assault Victimization Reporting Likelihood. (April 2023) - Stanek, Kayleigh A.; Fox, Kathleen A.; Telep, Cody W.; Trinkner, Rick
Sexual assaults are underreported to the police, even though this crime affects one in four college women. Using a vignette design, this study fills a gap in the literature by examining the influence of prior police perceptions, procedurally unjust treatment, and the sex of the responding officer on college women's likelihood to report sexual assault. Results indicate positive prior police perceptions significantly increase students' perceived likelihood to report sexual victimization. Even when controlling for prior perceptions, procedurally unfair treatment significantly decreases the likelihood of future victimization reporting. Responding officer sex does not affect students' decision to report.